2013
DOI: 10.1021/nl4024066
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Probe Maskless Lithography for 27.5 nm Half-Pitch Si Technology

Abstract: Thermal scanning probe lithography is used for creating lithographic patterns with 27.5 nm half-pitch line density in a 50 nm thick high carbon content organic resist on a Si substrate. The as-written patterns in the poly phthaladehyde thermal resist layer have a depth of 8 nm, and they are transformed into high-aspect ratio binary patterns in the high carbon content resist using a SiO2 hard-mask layer with a thickness of merely 4 nm and a sequence of selective reactive ion etching steps. Using this process, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 26 publications
2
66
0
Order By: Relevance
“…The obtained value for the 3 σ line edge roughness of 2.9 ± 0.5 nm is in agreement with the results obtained previously for 27.5 nm lines and spaces 7 . In this previous work we found that the LER was inversely proportional to the slope of the topographic patterns.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The obtained value for the 3 σ line edge roughness of 2.9 ± 0.5 nm is in agreement with the results obtained previously for 27.5 nm lines and spaces 7 . In this previous work we found that the LER was inversely proportional to the slope of the topographic patterns.…”
Section: Resultssupporting
confidence: 92%
“…Conversely thermal evaporation of SiO 2 on PMMA resulted in very smooth films, R a = 0.23 nm. Third, on the sputtered oxide we had to use a minimal imaging resist thickness of 20 nm in order to achieve a patterning depth of more than 5 nm 7,17 . On the evaporated oxide the thickness of the PPA imaging resist could be reduced to 9 nm.…”
Section: Introductionmentioning
confidence: 99%
“…2b). Patterning at a half pitch down to 10 nm without proximity corrections was demonstrated 27 . Other milestones towards technical readiness of the technique are the stitching of patterning fields at < 10 nm precision 30 and a high-quality pattern transfer into the underlying silicon substrate at high resolution and low line edge roughness (Fig.…”
Section: Thermal and Thermochemical Splmentioning
confidence: 99%
“…The smallest half-pitch feature of ~18 nm for a pattern transfer into Si for up to 65-nmdeep trenches which only have an edge roughness of 3 nm [130,131].…”
Section: Tip Nano-writingmentioning
confidence: 99%